Selective reaction monitoring approach using structure-defined synthetic glycopeptides for validating glycopeptide biomarkers pre-determined by bottom-up glycoproteomics. Issue 33 (3rd August 2022) - Shiratori, Kouta; Yokoi, Yasuhiro; Wakui, Hajime; Hirane, Nozomi; Otaki, Michiru; Hinou, Hiroshi; Yoneyama, Tohru; Hatakeyama, Shingo; Kimura, Satoshi; Ohyama, Chikara; Nishimura, Shin-Ichiro
Abstract : Structure-defined synthetic glycopeptides allow the validation of glycopeptide biomarkers pre-determined from bottom-up glycoproteomics based on the selective reaction monitoring approach. Abstract : Clusterin is a heavily glycosylated protein that is upregulated in various cancer and neurological diseases. The findings by the Hancock and Iliopoulos group that levels of the tryptic glycopeptide derived from plasma clusterin, 372 Leu-Ala-Asn-Leu-Thr-Gln-Gly-Glu-Asp-Gln-Tyr-Tyr-Leu-Arg 385 with a biantennary disialyl N -glycan (A2G2S2 or FA2G2S2) at Asn374 differed significantly prior to and after curative nephrectomy for clear cell renal cell carcinoma (RCC) patients motivated us to verify the feasibility of this glycopeptide as a novel biomarker of RCC. To determine the precise N -glycan structure attached to Asn374, whether A2G2S2 is composed of the Neu5Acα2, 3Gal or/and the Neu5Acα2, 6Gal moiety, we synthesized key glycopeptides having one of the two putative isomers. Selective reaction monitoring assay using synthetic glycopeptides as calibration standards allowed "top-down glycopeptidomics" for the absolute quantitation of targeted label-free glycopeptides in a range from 313.3 to 697.5 nM in the complex tryptic digests derived from serum samples of RCC patients and healthy controls. Our results provided evidence that the Asn374 residue of human clusterin is modified dominantly with the Neu5Acα2, 6Gal structure and the levels of clusterin bearing an A2G2S2 with homo Neu5Acα2, 6Gal terminals at Asn374 decrease significantly in RCC patients as compared with healthy controls. The present study elicits that a new strategy integrating the bottom-up glycoproteomics with top-down glycopeptidomics using structure-defined synthetic glycopeptides enables the confident identification and quantitation of the glycopeptide targets pre-determined by the existing methods for intact glycopeptide profiling.